Strategic innovation and sustainability in Indonesia's oil and gas industry: a hybrid systematic literature review and bibliometric analysis - Tandiarak Agustinus; Purba John Tampil (Enrichment : Journal of Management, 2025)
This study explores how strategic innovation and sustainability converge in transforming Indonesia’s oil and gas sector amidst the global energy transition. Using a hybrid methodology (Systematic Literature Review and bibliometric analysis of Scopus-indexed articles from 2014-2025), it maps significant research clusters, key contributors and emerging themes. A marked increase in publications following Indonesia’s 2022 NDC update evidences growing alignment among dynamic capabilities, strategic innovation and sustainable practices (Cherepovitsyn & Rutenko, 2022; Nurhidayah et al., 2024). Yet, a persistent gap remains between corporate sustainability commitments and actual operational transformation. The paper’s contribution lies in integrating Dynamic Capabilities Theory, Strategic Innovation Theory and Sustainability Transitions Theory into a unified framework to support a just, innovative and sustainable energy future.